2015
DOI: 10.4172/1948-5948.s7-001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fungal Growth and Fusarium Toxins by Selected Cultures of Lactic Acid Bacteria

Abstract: Two species of Lactobacilli (Lactobacillus rhamnosus and Lactobacillus paracasie subsp. paracasie) were tested for their ability to inhibit growth and mycotoxins production by three species of Fusarium, (F. graminearum, F. culmorum and F. proliferation) which are the main producers of mycotoxins deoxynivalenol, zearalenone and fumonisin B1, respectively. L. paracasie subsp. paracasie was found to be effective in reducing the amount of toxins produced, although fungal growth was not affected. The inhibition lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Paracasie after 20-day incubation (70.5 µl/ml compared with 300 µl/ml FB 1 in the control group) and L. para casie subsp. Paracasie could inhibit FB 1 production in a 10-day incubation period (Gomah and Zohri, 2014). Becker et al (1997) reported that FB 1 was not degraded by Enterococcus faecium while the binding of FB 1 and FB 2 , up to 24 and 62%, respectively by Enterococcus sp.…”
Section: Resultsmentioning
confidence: 98%
“…Paracasie after 20-day incubation (70.5 µl/ml compared with 300 µl/ml FB 1 in the control group) and L. para casie subsp. Paracasie could inhibit FB 1 production in a 10-day incubation period (Gomah and Zohri, 2014). Becker et al (1997) reported that FB 1 was not degraded by Enterococcus faecium while the binding of FB 1 and FB 2 , up to 24 and 62%, respectively by Enterococcus sp.…”
Section: Resultsmentioning
confidence: 98%
“…Franco et al (2011) showed that LAB isolated from wheat derivatives and kefir grain were capable of inhibiting the fungus Fusarium graminearum. Gomah and Zohri (2014) demonstrated that L. rhamnosus presented activity against growth of F. graminearum, Fusarium culmorum, and Fusarium proliferatum, which are the main producers of DON, ZEA, and FB1 mycotoxins, respectively. The presence of the bacteria completely suppressed mycelium growth of all the Fusarium species studied and consequently inhibited production of toxins.…”
Section: Metals and Metalloidsmentioning
confidence: 99%
“…Also, Piotrowska and Zakowska (2005) screened the ability of some Lactobacillus strains to reduce the concentration of ochratoxin A or remove it from liquid medium. Gomah and Zohri (2015) found that Lactobacillus paracasie subsp. paracasie inhibited the production of deoxynivalenol, zearalenone and fumonisin B 1 production to 56.8, 73.0 and 76.5%, respectively and also, Lactobacillus rhamnosus completely suppressed the mycelium growth of some Fusarium species and consequently, no toxin was produced in the presence of this bacterium.…”
Section: Introductionmentioning
confidence: 99%